Young children representing data - Joana Ribeiro; Ema Mamede (European Teacher Education Network, 2019)
The study aimed to understand young children's ideas (4-6-year-olds, N=24) when collecting, organizing and representing data. It focuses on: 1) How do children understand data collection and organization? 2) What sort of difficulties do children have when representing data? A six sessions intervention was implemented, in which children worked with real objects and graphs (real and pictures). A qualitative analysis was used to explore children's ideas related to data representation. Results show that children are able to collect and organize data; and they can interpret information from a simple real graph and translate it into a pictogram, with understanding.